2009
DOI: 10.1007/s11403-009-0053-y
|View full text |Cite
|
Sign up to set email alerts
|

The shared reward dilemma on structured populations

Abstract: In this paper we study the recently introduced "shared reward dilemma" (Cuesta et al. in J Theor Biol 251:253 263, 2008) in the presence of a structure governing the interactions among the population. The shared reward dilemma arises when the prisoner's dilemma is supplemented with a second stage in which a fixed reward is equally distributed among all cooperators. We first extend our previous results on the equilibrium structure of this game to the case of a one-shot game taking place on a regular network. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…equity, and the effective distribution of resources. In line with reference [11], it will also be demonstrated that residents within the condominium community may prioritize their self-interests and opportunistic behaviors over collective well-being. They can act in their own self-interest, potentially leading to outcomes where collective well-being is compromised in favor of personal gain.…”
Section: The "Social Choice Theory"mentioning
confidence: 57%
“…equity, and the effective distribution of resources. In line with reference [11], it will also be demonstrated that residents within the condominium community may prioritize their self-interests and opportunistic behaviors over collective well-being. They can act in their own self-interest, potentially leading to outcomes where collective well-being is compromised in favor of personal gain.…”
Section: The "Social Choice Theory"mentioning
confidence: 57%
“…It is worthwhile to point out that, in the generalized 𝑁-person volunteer's dilemma, the public good is produced or safeguarded as a step function of individual contributions. This function thus differs from the linear function used in some previous works (Cuesta et al, 2008;Jiménez et al, 2008;Jiménez et al, 2009) on the 𝑁-person prisoner's dilemma game. In comparison to the case considered here, the N-person prisoner's dilemma can be considered as an extreme case, which − due to the assumed linearity − cannot capture the effects of thresholds for the production of the public good.…”
Section: Comparison With Related Studiesmentioning
confidence: 92%
“…In this setting, players interact through a game, while cooperators can also receive an additional payo coming from an exogenous source available only to them and not to defectors. This updated model therefore incurs a new dilemma: individuals may prefer to choose the shared reward despite the possibility of being exploited by defectors; on the other hand, if too many players do that, cooperators will gain a poor reward and defectors will thus outperform them [39]. Besides, a growing number of field and experimental studies focus on solving collective action problems [40][41][42].…”
Section: Conclusion 13mentioning
confidence: 99%